KARAKTERISASI DAN UJI AKTIVITAS BAKTERI RIZOSFER LAHAN ULTISOL SEBAGAI PEMACU PERTUMBUHAN TANAMAN DAN AGENSIA HAYATI CENDAWAN PATOGEN TULAR TANAH SECARA IN VITRO - Andi Khaeruni, Gusti Ayu Kade Sutariati & Sri Wahyuni . (Universitas Lampung, 2010)
Characterization and activities assay of rhizosphere bacteria from ultisol land for plant-growth promoting and biocontrol agents of soil-borne fungus pathogens under in vitro test. Although many studies have been conducted to identify the specific traits of the plant growth-promoting and bioprotecting rhizobacteria (PGPBR), they were limited to studying specific PGPBR isolates from ultisol lands. We selected 273 isolates from bulk soil and plant rhizosphere and examined them for a wide array traits that might inhibit the growth of plant pathogens and increase early cucumber growth in ultisol soil. A subsample of 25 isolates, all positively produce chitinase and sellulose enzymes, 18 positively produce protease and 7 were fluorescens on KB medium under UV lighting. All isolates could produce IAA and be able to solubilize phosphor in vitro test, 10 exhibited low level of nitrogenase activity. Futher test showed that out of 25 isolates, 12 inhibited F. oxysporum, P. capsici, R. solani and S. rolfsii in vitro. All isolates increased seed germination, but only 5 isolates significanty increased early cucumber growth in ultisol soil. The results suggest that rhizobacteria be able to produce extracelluler enzymes, siderophore, ACC deasiminase, and IAA or those which are able to solubilize phosphor in vitro may be potential to be uses as biofertilizer and biological control agents in ultisol land.